The pricing of G7 sovereign bond spreads: the times, they are a-changin - Antonello D'Agostino; Michael Ehrmann (European Central Bank (ECB), 2013)
Against the background of the current debate about fiscal sustainability in several advanced economies, this paper estimates determinants of G7 sovereign bond spreads, using high-frequency proxies for market expectations about macroeconomic fundamentals and allowing for time-varying parameters. The paper finds substantial asymmetry in the importance of country fundamentals and considerable time variations in the pricing of risks. There has been a reduced pricing of several risk factors in the years preceding the financial crisis, and either an overpricing of risk or the pricing of a re-denomination risk of euro area bonds during the European sovereign debt crisis.
Keywords: E43; E44; F34; G15; 330; Fiscal Policy; Sovereign Spreads; time-varying coefficients